2017
DOI: 10.1111/scs.12489
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, physical, mental and social factors in the cessation of breastfeeding before 6 months: a systematic review

Abstract: Sociodemographic factors appeared to have caused cessation of breastfeeding in some of the included articles. The preventive work should focus on how to improve the knowledge of healthcare professionals and targeted interventions must address mothers who are at risk of ceasing breastfeeding before the recommended time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 47 publications
5
37
0
9
Order By: Relevance
“…In addition, high maternal education level was positively associated with the duration of partial breastfeeding. This reaffirms previous research findings that mothers with high level of education and mothers with previous children are more likely to breastfeed [10,35]. Previous breastfeeding experience improves the ability to breastfeed, and parents with high level of education might have more flexibility regarding use of parental leave days, especially during the child's second year [36].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, high maternal education level was positively associated with the duration of partial breastfeeding. This reaffirms previous research findings that mothers with high level of education and mothers with previous children are more likely to breastfeed [10,35]. Previous breastfeeding experience improves the ability to breastfeed, and parents with high level of education might have more flexibility regarding use of parental leave days, especially during the child's second year [36].…”
Section: Discussionsupporting
confidence: 88%
“…A recent systematic review employed stringent inclusion and exclusion factors to examine a large number of sociodemographic, physical, maternal, and social factors in relation to breastfeeding in the first 6 months but did not include a quantitative analysis. 63 Although our review and meta-analysis focused on a more limited number of factors that had a relatively large volume of high-quality literature, many factors were not included. In our initial search, we expected to identify infant birth factors such as hypoglycemia, jaundice, birth weight, and gestational age, but found very little published data meeting our inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In a U.S. study, total maternity leave available (summing fully paid, partially paid, and unpaid) was not clearly related to breastfeeding initiation or duration, but maternal return to work before 12 weeks (partially or full-time) or full-time after 12 weeks was related to reduced breastfeeding duration (Mandal et al, 2010). However, a recent review highlighted that the level of evidence for the association between early cessation of breastfeeding and a return to work within 12 weeks post-birth is low (Mangrio, Persson, & Bramhagen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a U.S. study, total maternity leave available (summing fully paid, partially paid, and unpaid) was not clearly related to breastfeeding initiation or duration, but maternal return to work before 12 weeks (partially or full‐time) or full‐time after 12 weeks was related to reduced breastfeeding duration (Mandal et al, ). However, a recent review highlighted that the level of evidence for the association between early cessation of breastfeeding and a return to work within 12 weeks post‐birth is low (Mangrio, Persson, & Bramhagen, ). Data from the U.K. Millennium Cohort Study (Hawkins, Griffiths, Dezateux, & Law, ; Hawkins, Griffiths, Dezateux, & Law, ) found that mothers who were employed full‐time were less likely to initiate breastfeeding than were women who were students or not employed.…”
Section: Introductionmentioning
confidence: 99%